2006
DOI: 10.1002/jsfa.2541
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and acid concentrations in 98 grape cultivars analyzed by principal component analysis

Abstract: A total of 98 grape cultivars were studied for content and composition of organic acids and sugars in grape juice during two consecutive years. Glucose and fructose were the predominant sugars in grape berries and ranged from 45.86 to 122.89 mg mL −1 , and 47.64 to 131.04 mg mL −1 , respectively, in two years. Sucrose was present at trace amounts in most cultivars, but two cultivars of hybrids between Vitis labrusca and V. vinifera contained large amounts of sucrose. Tartaric acid content in berries, varying f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
139
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(172 citation statements)
references
References 20 publications
29
139
1
3
Order By: Relevance
“…The lowest and the highest contents of total sugars were found out in the cvs Riesling and Hibernal (190.31 g/l and 244.49 g/l, respectively). Liu et al (2006) found out in 98 cultivars the range of glucose content within the limits of 45.86 g/l and 122.89 g/l while the content of fructose ranged from 47.64 g/l to 131.04 g/l.…”
Section: Resultsmentioning
confidence: 92%
“…The lowest and the highest contents of total sugars were found out in the cvs Riesling and Hibernal (190.31 g/l and 244.49 g/l, respectively). Liu et al (2006) found out in 98 cultivars the range of glucose content within the limits of 45.86 g/l and 122.89 g/l while the content of fructose ranged from 47.64 g/l to 131.04 g/l.…”
Section: Resultsmentioning
confidence: 92%
“…The involvement of VvSK1 in the control of sugar compartmentation was further strengthened by the fact that cells overexpressing VvSK1 accumulate twice more Glc and three times more Suc than the control, whereas the starch content remains unaffected. Sugar levels of suspension cells significantly differ from those in berries, where monosaccharide concentrations can reach 1.5 M, whereas Suc is poorly detectable (Fillion et al, 1999;Liu et al, 2006). In this context, the role of VvSK1 on sugar transport and accumulation in grape berries has to be further investigated by altering VvSK1 expression in berries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nutritive and functional properties are becoming more and more important in determining consumer choice, even if the classical parameters such as soluble solids concentration (SSC), acid contents, SSC/acid ratio and skin color are still the main quality parameters in table grapes. [2][3][4][5][6][7][8] In particular for colored grapes, skin color is a quality factor of fundamental importance, since sight is the first of the senses to be used, and visual appreciation is decisive in the choice. [9] The total content of anthocyanins and the proportions between them, dependent mainly on the cultivar, [10] determine the final coloration of the grape skin.…”
Section: Introductionmentioning
confidence: 99%